Ein anderer Mensch werden: Johann Arndts Verständnis der imitatio Christi als Anleitung zu einem wahren Christentum - Illg, Thomas (Studien zur Kirchengeschichte Niedersachsens, 2011)
The devotional literature of Johann Arndt (1555-1621) had an extraordinarily broad impact. To guide his readers toward spiritual renewal was the principle concern of his works. Arndt's doctrine of the imitation of Christ is of central significance in this respect. The study of the concept of imitation of Christ reveals the fascinating profile of the theologian and his endeavour to unite partly disparate traditions in one concept. Besides Lutheran theology the volume especially discusses Paracelsus and his school of followers, Valentin Weigel, and medieval mystic sources. It includes a comparative study of the different versions of the book Vom wahren Christentum (True Christianity) that were printed between 1605 and 1610. Arndt's Passion Sermons and other selected texts are included in the analysis. Comparisons with writings of Johann Gerhard and Valentin Weigel highlight distinctive aspects of Arndt's theological profile